Borehole density on the surface of living Porites corals as an indicator of sedimentation in Hong Kong. Issue 1 (15th July 2016) - Xie, James Y.; Wong, Jane C.Y.; Dumont, Clement P.; Goodkin, Nathalie; Qiu, Jian-Wen
Abstract: Borehole density on the surface of Porites has been used as an indicator of water quality in the Great Barrier Reef. We assessed the relationship between borehole density on Porites and eight water quality parameters across 26 sites in Hong Kong. We found that total borehole densities on the surface of Porites at 16 of the studied sites were high (> 1000 individuals m − 2 ), with polychaetes being the dominant bioeroders. Sedimentation rate was correlated positively with total borehole density and polychaete borehole density, with the latter relationship having a substantially higher correlation of determination. None of the environmental factors used were significantly correlated with bivalve borehole density. These results provide a baseline for assessing future changes in coral bioerosion in Hong Kong. This present study also indicates that polychaete boreholes can be used as a bioindicator of sedimentation in the South China Sea region where polychaetes are numerically dominant bioeroders. Highlights: We explored the relationship between water quality and the density of coral borers. Borehole densities on Porites at 62% the studied sites in Hong Kong are high. Borehole density can be used as an indicator of sedimentation.